Mitigate+: Vietnam Living Labs Site Selection - Nelson, Katherine (International Rice Research Institute, 2022)
The presentation discussed the candidate geography or transect (and at what scale) for the Mitigate+ Living Labs project in Can Tho/Mekong Delta, including the characteristics of the site’s food system and key sectors, set of problems, possible co-benefits and for whom, and key local implementing partners